Silence has no place: a framing analysis of corporate statements about racial inequity, immigration policy and LGBTQ rights. (2nd November 2021) - Sterbenk, Yvette M.; Ward, Jamie; Luttrell, Regina; Shelton, Summer
Abstract : Purpose: This study explores the framing of messages delivered by 105 Fortune 500 companies across 21 sectors in June 2020 in response to three social justice issues that took prominence that month in the United States: racial inequity, immigration laws and LGBTQ rights. Design/methodology/approach: Researchers compiled a list of the top five companies in each sector on the 2020 Fortune 500 list, with a resulting list of N  = 21 sectors and N  = 105 companies. A database of corporate statements was compiled along with a comprehensive list of recurring themes. Quantitative framing analysis was used to examine each corporate statement. Findings: Seventy percent of the companies examined made statements about the issue of racial injustice, 58% about LGBTQ issues and only 6% about immigration policy. Coders identified the most frequent message type coded on each social justice issue: racial inequity –"Working Together"; immigration policy – "Celebration"; LGBTQ rights – "Celebration." Research limitations/implications: This study relied on a quantitative analysis of themes, but it did not analyze the specific language or media used. Further examination of rhetorical choices could uncover additional meanings in the messages. Practical implications: Companies are increasingly called upon to speak out on controversial issues. This can be challenging for communicators who are deciding how to respond. This study sheds light on the common frames used in corporate statements. Originality/value: No studies to date have adopted a content analysis approach to assess the content of corporate activist statements. Examining the messages is important because, as more companies become increasingly vocal about social issues, stakeholders utilize this information to judge the sincerity of both the company and the message.